(untitled) (Transport systems and technologies, 2023)
The experience of operating switches shows that load-bearing elements fail for two main reasons: defects and wear. The percentage failure of elements due to one reason or another depends on the operating conditions in which they operate. In this case, the most worn elements of switches are pointers and point frogs and their service life is determined by the amount of tonnage passed through them before reaching the standard values of wear or the appearance defects. The article is devoted to the study of wear resistance of switches operated in various transport systems, namely, mainline transport and subways. The article considers the issues of predicting the standard service life cross elements of typical angles using operational studies for subway conditions and a new theoretical methodology based on the analysis of switches withdrawn from operation after they reach the standard wear values for mainline transport. For analytical calculations, the method of modeling the interaction process and graph-analytical methods were used. As a result of the study, the analytical equations predictive curves for the formation vertical wear as a function of the passed tonnage for the switches point frogs operated on lines of mainline railway transport and the Kyiv subway were established.